Pandemic Marine Risks Assessment for Marine Spatial Planning (MSP): A Case Study of Northport, Malaysia - Ayati Parmen; Nazirah Mohamad Abdullah; Badrul Hisham Ismail; Yusuf Drisu Opaluwa (International Journal of Sustainable Construction Engineering and Technology, 2024)
The pandemic outbreak has emphasized the necessity of incorporating pandemic marine risk assessment as a critical component of marine spatial planning (MSP). The purpose of this study was to utilize the Risk Assessment Matrix (RAM) methodology to determine the most severely impacted zone at Northport, Port Klang. 31 senior management personnel at Northport, Port Klang were involved in a survey to assess the pandemic's severity in various zones. According to the findings, the Vehicle's Terminal zone had the highest score of 17.72, indicating it to be the most severely impacted zone, followed by the Passenger's Terminal zone (15.88), Distribution Centre zone (14.62), Bulk zone (14.52), Dangerous Good zone (14.13), Free Zone (14.10), Ancillary Service zone (13.65), and Container zone (13.39). These results can be integrated into Geographical Information System (GIS) and Multi Criteria Decision Analysis (MCDA) to convert them from numerical values to spatial data, and visualize them hierarchically. Additionally, this study's findings can contribute to enhancing MSP practices, not only at Northport, Port Klang, but also at other ports facing similar challenges. By including pandemic risk assessment as a crucial part of MSP, ports can develop effective pandemic response plans that prioritize the health and safety of port workers and visitors, as well as ensure the continuity of trade and economic activities.